A Church, a Bar, and a Brewery : Prohibition and Ethno-Religious Identities in Berlin, Wisconsin, 1910-1933 - Schroeder, Danielle Ann (My University, 2015)
In the mid nineteenth-century, large numbers of German and Polish immigrants began to arrive in Wisconsin, and they brought with them customs of beer and liquor-drinking. In response to the turbulent changes the country was undergoing, middle-class, native-born, and Protestant Americans started a grass-roots movement against the alcohol intemperance of immigrants and the working-class. The culmination of their efforts was the ratification of the Eighteenth Amendment in 1919. This paper studies how the residents of Berlin, a small, central-northeastern Wisconsin city with a heavy German-Polish population, reacted to Prohibition. Religious, ethnic, and class identities play a significant role in Americans' relationship with alcohol and drinking. Therefore, this paper analyzes the demographic make-up of Berlin, and points out ways that identity influenced Berlinites' stances on federal and statewide Prohibition. With information gathered from census data, temperance organization records, newspapers, circuit court records, and election data, this study pieces together the story of Prohibition within a small Wisconsin community.
Keywords: Berlin (Wis.); Prohibition -- Wisconsin